Spatial determinants of sectors wage inequaities: Analysis for the region of Croatia - Vinko Mustra; Blanka Škrabić; Paško Burnać (European Regional Science Association (ERSA), 2010)
The regional studies have shown that regional disparities within the countries appear to persist or even to grow. One of the most important indicators of the disparities is regional wage level. It is widely accepted that spatial effects have a different impact among sectors in developed countries. The traditional core-periphery pattern of manufacturing is weakening which tends to work towards regional convergence and on the other hand service industries continue to concentrate in high-density areas thus reinforcing divergence. However, there is less evidence for these effects for developing countries. This paper uses NUTS3 sub-regional data for Croatia from year 2000 onward to investigate the sources of the regional wages differences on the sector level. The recent literature recognizes two main determinants of spatial differences in wages; namely, the productivity and occupational composition. Therefore the paper uses shift-share analysis to decompose the spatial variation of wages into productivity effect and occupational composition effect exploring how the spatial variance in wages is attributable to variations in these effects among different sectors. The paper also examines the relationship between these two determinants of spatial differences and the proximity to economic mass instrumented by different measures of urbanization in the NUTS3 sub-regions.
Keywords: 330